2000
DOI: 10.1016/s0550-3213(00)00448-x
|View full text |Cite
|
Sign up to set email alerts
|

Spectral universality of real chiral random matrix ensembles

Abstract: We investigate the universality of microscopic eigenvalue correlations for Random Matrix Theories with the global symmetries of the QCD partition function. In this article we analyze the case of real valued chiral Random Matrix Theories (β = 1) by relating the kernel of the correlations functions for β = 1 to the kernel of chiral Random Matrix Theories with complex matrix elements (β = 2), which is already known to be universal. Our proof is based on a novel asymptotic property of the skew-orthogonal polynomia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 76 publications
1
14
0
Order By: Relevance
“…and it follows from the definitions of the resolvent and eigenvalue density, (33) and (34), with [40][41][42]…”
Section: A Large C 2 -Approximation For Choementioning
confidence: 99%
“…and it follows from the definitions of the resolvent and eigenvalue density, (33) and (34), with [40][41][42]…”
Section: A Large C 2 -Approximation For Choementioning
confidence: 99%
“…of the eigenvalues of the Euclidean Dirac operator / Dψ k = λ k ψ k in QCD [2,3]. The spectral density for small eigenvalues is in fact determined completely by the symmetries of the QCD partition function: The chiral symmetry breaking pattern, and the axial symmetry due to which all non-zero eigenvalues appear in pairs ±λ k .…”
Section: Random Matrix Theorymentioning
confidence: 99%
“…In a parallel development it was shown that the spectral density of the Dirac operator for a gauge theory near its zero eigenvalues should only depend on the symmetries in question [17][18][19]. Although the original work [17][18][19] used a Gaussian random matrix model, the results from the random matrix theory can be proven to be universal [20][21][22][23][24]. This implies that the spectral density of the Dirac operator near the origin can be extracted from random matrix theories which provide a description of common aspects of various quantum phenomena (for a review see [25]).…”
Section: Introductionmentioning
confidence: 99%